(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In India, the scenario has completely changed right after the Demonetization. It was the major step taken by the government to make India cashless. The present paper studied the trend and pattern of Electronic Transactions through different methods after demonetization. The study also throws light on the main benefits and challenges for the government associated with the adoption of cashless system in India. The study concluded that there is lot more to be done on the part of government like, developing strong banking base, public awareness programmes, etc for the achievement of goal of India to be a Cashless society.